2022
DOI: 10.1080/14756366.2022.2102005
|View full text |Cite
|
Sign up to set email alerts
|

The old worldsalsolaas a source of valuable secondary metabolites endowed with diverse pharmacological activities: a review

Abstract: Salsola is an important genus in the plant kingdom with diverse traditional, industrial, and environmental applications. Salsola species are widely distributed in temperate regions and represent about 45% of desert plants. They are a rich source of diverse phytochemical classes, such as alkaloids, cardenolides, triterpenoids, coumarins, flavonoids, isoflavonoids, and phenolic acids. Salsola spp. were traditionally used as antihypertensive, anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…Widely distributed in arid and semi-arid regions of the world (ElNaggar & al. 2022), the genus Salsola is represented in Algeria by 11 species and varieties (Quézel & Santa 1962–1963) to 22 species and subspecies (Dobignard & Chatelain 2010–2013).…”
Section: Discussionmentioning
confidence: 99%
“…Widely distributed in arid and semi-arid regions of the world (ElNaggar & al. 2022), the genus Salsola is represented in Algeria by 11 species and varieties (Quézel & Santa 1962–1963) to 22 species and subspecies (Dobignard & Chatelain 2010–2013).…”
Section: Discussionmentioning
confidence: 99%
“…This group is represented by moupinamide (Ntrans-feruloyltyramine, 1.22), which was reported in several Salsola species. 15,44 Other derivatives such as cinnamoyl (1.19), S1 † and Fig. 2).…”
Section: Alkaloids and Nitrogenous Compoundsmentioning
confidence: 99%
“…19 Various plant species within the Old-World Salsola genus have been documented for their ability to exhibit antimicrobial effects against diverse pathogens. 15 Hence, in the present research, we investigated the antibacterial properties of C. volkensii and claried its capabilities in inhibiting biolm formation and disrupting quorum sensing in clinical isolates of Pseudomonas aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, diallyl disulfide had beneficial effects on establishment of microbiota biofilms and colonic mucus production that alleviate murine colitis ( Motta et al, 2015 ). Coumarins are a class of organic compounds which are not only isolated from sieve bean, but also in many different plants, such as Tonka beans, verbena, wild vanilla and orchid ( ElNaggar et al, 2022 ). Studies found that some coumarins including esculetin and furocoumarins have broad range anti-biofilm activity by disturbing QS in S. aureus , E. coli , S. typhimurium , and P. aeruginosa via reduction of AHL ( Girennavar et al, 2008 ; Dürig et al, 2010 ).…”
Section: Quorum Sensingmentioning
confidence: 99%
“…Coumarin is found in tonka beans, verbena, wild vanilla and orchid, and has the smell of fresh hay and fenugreek ( ElNaggar et al, 2022 ). Coumarins have been shown to have antibacterial activity as a QSI in a broad spectrum of pathogens.…”
Section: Nucleotide-based Second Messengersmentioning
confidence: 99%